2016
DOI: 10.1111/ruso.12106
|View full text |Cite
|
Sign up to set email alerts
|

Rural Agricultural Change and Individual Out‐migration

Abstract: We investigate the impact of household use of labor‐saving farm technologies on first‐time out‐migration after the household agriculture and consumption survey was conducted in 1996. Building on the labor substitution framework, we hypothesize that household use of labor‐saving technologies (e.g., tractors, farm implements, chemical fertilizers, and pesticides) increases individual out‐migration. To estimate the effects of the use of labor‐saving farm technologies on out‐migration, we use uniquely detailed pan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 57 publications
1
23
0
Order By: Relevance
“…Both coefficients of the modern technology are higher, leaving the question whether the new technology is labor saving. Observations in many countries document that in the course of modernizing of the agricultural sector migration into cities can be observed, which indicates that agricultural technical progress is labor saving (Bhandari and Ghimire 2016). Therefore, we assume that L m < L t .…”
Section: Box 33 What Are the Motives Of The Dog In The Manger?mentioning
confidence: 99%
“…Both coefficients of the modern technology are higher, leaving the question whether the new technology is labor saving. Observations in many countries document that in the course of modernizing of the agricultural sector migration into cities can be observed, which indicates that agricultural technical progress is labor saving (Bhandari and Ghimire 2016). Therefore, we assume that L m < L t .…”
Section: Box 33 What Are the Motives Of The Dog In The Manger?mentioning
confidence: 99%
“…It is important to note that some international research, particularly in places that tend to serve global economic development rather than grow rich from it-for example from rural parts of Asia and Latin America (e.g. Azaola, 2012;Barney, 2012;Bhandari & Ghimire, 2016; Brown, Scrase & Granguly-Scrase, 2017)-foregrounds economic motivators and constraints, examining young people who are propelled away from their rural communities in search of jobs and remittance income as the economies of their home communities restructure and globalize.…”
Section: Young People Move For a Complex MIX Of Subjective Personal mentioning
confidence: 99%
“…Recently, Chitwan has experienced dramatic changes in population mobility, transitioning from a frontier destination for in-migrants from surrounding hill districts of Nepal to one of the country's major migrant-sending districts (Bhandari, 2004;Bhandari & Ghimire, 2016). According to 2011 census, as many as 29% (27% for Nepal) of the households reported that at least one member was absent from household.…”
Section: Methodology the Settingmentioning
confidence: 99%
“…Previous migration research in Nepal primarily focused on the causes of out-migration, in general (Bhandari, 2004, Bhandari & Ghimire, 2016Bohora-Mishra, 2013;Bohora-Mishra & Massey, 2009;2011;Gurung, 2012;Piotrowski, 2013;Piotrowski et al, 2013;Shrestha & Bhandari, 2007;Williams, 2009;. Kern & Muller-Boker (2015) provide a detailed description of the process and the role of recruitment agencies on Nepali migration.…”
Section: Introductionmentioning
confidence: 99%